How well does CO emission measure the H2 mass of MCs? - Szűcs, László; Glover, Simon; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2016)
Abstract. We present numerical simulations of molecular clouds (MCs) with self-consistent CO gas-phase and isotope chemistry in various environments. The simul